Automated marking of linear algebraic equation using n-gram method / Arsmah Ibrahim ... [et al.] - Ibrahim, Arsmah; A Bakar, Zainab; Othman, Nuru'l - 'Izzah; Ismail, Nur Fuzaina (Universiti Teknologi MARA (UiTM), 2007)
This paper demonstrates the basic feasibility of using n-gram string matching method to grade on a set of four linear algebraic equations. The degree of correctness between the worked-out solutions submitted by respondents and the solutions schemes provided by the examiner is measured using Dice coefficient. Experiments have been conducted on 180 respondents for each question. The scores obtained by n-gram method are compared with the manually marked scores. The n-gram method is proven to be suitable when applied to these four linear algebraic equations as its performance is satisfactory and the results suggest feasibility. It is also realized that n-gram method has the advantage of producing uniformity and consistency.